Driving Factors of Zakat Payment by The Farmers to the Development of Sharia Economy-Based Rural:: Case Study in Wonosobo, Central Java, Indonesia - Yuni Yulia Farikha (Department of Islamic Economics, Postgraduate Program, UIN Kiai Haji Achmad Siddiq, Indonesia, 2018)
Abstract: Farmers can also be a driver of zakat payments for their community. In Indonesia, the potato farmers in Dieng Plateu, Wonosobo, Central Java, have practiced it more than 30 years. This paper would like to explore the practice of zakat in Kalilembu Village in Dieng Plateau by inquiring the driving factors of the farmers to pay zakat. Through qualitative approach, this study distributes questionnaire and interview the farmers who routinely pay zakat. This study deduces that the driving factors of the farmers to pay zakat are: religious motivation, economic, governance of zakat, and zakat payer satisfaction. This study recommends the zakat payments by farmers in this village become a role model for the development of sharia economy-based rural with the community as a prime driver. JEL Classification: O18, P25, R51, Z12